The representation of sadness and chaos through the metaphorical elements of nature in Campos de castilla (1912) by Antonio Machado - Arroyo Carvajal, Yordan (2019)
In this article an analysis is presented around the elements of the field such as, for example, the earth, the rivers, the scree, among others, that are used metaphorically in Campos de Castilla (1912), to give a negative nuance or distressing the bucolic space of the poems, which in turn marks or influences the mood of the lyric self. In this study, we take into account the convulsive socio-historical backdrop in Spain during the late nineteenth and early twentieth centuries. In order to associate text-society, the theory of socio-criticism is taken into account. In turn, the elements of nature, immersed in the poems are analyzed from the symbolism, using as base the dictionaries of Chevalier and Cirlot symbols.